Pemanfaatan Pelayanan Kesehatan Pada Pasien Rawat Jalan Di Puskesmas Bontang Selatan 1 - Gloria Priska Britani Sumlang; Ratno Adrianto; Sumarni; Chaerunnisa AR; Irfansyah Baharuddin Pakki (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2025)
The utilization of healthcare services is a key indicator of a region’s health system effectiveness. Puskesmas, as a primary healthcare facility, plays a vital role in ensuring access to medical services. However, outpatient service utilization in Indonesia remains low, at 35.16% in 2023, and only 33.39% in East Kalimantan. Puskesmas Bontang Selatan 1 has seen an increase in outpatient visits, yet the Community Satisfaction Survey (SKM) indicates fluctuations, particularly in requirements, procedures, and service convenience. These issues may affect future service utilization. This study analyzes factors influencing healthcare service utilization among outpatients at Puskesmas Bontang Selatan 1 in 2024. The research employs a quantitative analytical survey with a cross-sectional approach. The sample consists of 100 outpatients, selected through Proportional Stratified Random Sampling. Data analysis was conducted using univariate and bivariate methods with Fisher’s Exact Test. Findings show significant associations between healthcare availability (p = 0.018), socio-psychological factors (p = 0.000), and information accessibility (p = 0.002) with healthcare utilization, while doctor services (p = 0.140) showed no significant relationship. It is recommended that Puskesmas improve service information clarity, utilize waiting time for health education, and enhance service quality to increase healthcare utilization.